Extensions of a result by G. Talenti to (p, q)-Laplace equations. (March 2019) - Emamizadeh, Behrouz; Liu, Yichen; Porru, Giovanni
Abstract: We prove a comparison result for solutions to (p, q)-Laplace equation via Schwarz symmetrization. For the p-Laplace equation, the corresponding result is due to Giorgio Talenti. In a special (radial) case we also prove a reverse comparison result.